2015
DOI: 10.3844/ojbsci.2015.152.161
|View full text |Cite
|
Sign up to set email alerts
|

Hide Dehairing and Laundry Detergent Compatibility Testing of Thermostable and Solvents Tolerant Alkaline Protease from Hot Spring Isolate <i>Bacillus cohnii</i>U3

Abstract: Abstract:In the present study, alkaline protease producing thermophilic Bacillus cohniiU3 strain was isolation from Unnai hot spring, India. The maximum production of protease (344 U/mL) was reported after 72 h of inoculation at 50°C in shake flask culture using the gelatin casein medium. The protease was found to remain active up to 96 h and production was growth dependent. The activity of parital purified protease was reported in abroad range of pH ranging from 4.0 to 11.0 with an optimum of 9.0 pH; Enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Dehairing activity was performed by the method described by (Dudhgara et al 2015). Sheepskin was cut 3 × 2 cm pieces and washed gently with tap water and then rinsed with distilled water to remove chemicals from the skin, which may hinder enzyme activity during dehairing ac tivity.…”
Section: Dehairing Activitymentioning
confidence: 99%
“…Dehairing activity was performed by the method described by (Dudhgara et al 2015). Sheepskin was cut 3 × 2 cm pieces and washed gently with tap water and then rinsed with distilled water to remove chemicals from the skin, which may hinder enzyme activity during dehairing ac tivity.…”
Section: Dehairing Activitymentioning
confidence: 99%
“…Thermotolerant bacteria have attracted industrial and biotechnological attention as their enzymes are well suited for harsh industrial processes (Abdel-Rahman et al, 2016;Archna et al, 2015;Verma et al, 2015). Proteases obtained from thermophilic or thermotolerant (Adhikari et al, 2015;Bozoglu et al, 2015;Lele and Deshmukh, 2016;Panda et al, 2013;Remigio et al, 2012;Verma et al, 2014) bacteria, for example, have found applications such as hide dehairing in the leather industry and stain removal in laundry detergents (Chandrashekhar and Narayan, 2015;Dudhgara et al, 2015;Jaouadi et al, 2013). Cellulases have showed great potential in the production of bioethanol and other speciality chemicals from renewable agricultural residues (Hardiman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%